Leveraging management accounting for strategic decision making: Key drivers and performance impact in Vietnamese mechanical manufacturing firms - Vu, Nguyen Thanh; Trang, Nguyen Quynh; Hoai, Pham Thi Thu (Edelweiss Applied Science and Technology, 2025)
The Vietnamese mechanical manufacturing sector is a cornerstone of the country’s industrial economy, facing intense competition and rapid technological changes. Despite the critical role of strategic decision-making in these enterprises, research on management accounting practices in this sector remains limited, especially regarding factors influencing its adoption and impact on firm performance. This study addresses the gap by analyzing the application of management accounting for decision-making (MAMD) within the unique context of Vietnamese mechanical manufacturing enterprises (VMMEs). This research aims to identify and evaluate key factors influencing the adoption of MAMD in VMMEs and to quantify its impact on both financial and operational performance metrics. By doing so, the study seeks to provide empirical evidence on the strategic benefits of MAMD, contributing to an enhanced understanding of management accounting as a tool for driving competitiveness and performance in emerging economies. The study employs Structural Equation Modeling (SEM) to analyze data collected through structured surveys from a sample of 79 VMMEs, selected from the Vietnam Association of Mechanical Industry (VAMI) across three key sub-sectors: machinery, auto/vehicle components, and electronics manufacturing. Responses were gathered from 232 senior executives, chief accountants, and workshop foremen, ensuring comprehensive insights into strategic, financial, and operational dimensions. Results reveal that manufacturing technology, market competition, and accountants’ competencies significantly influence MAMD adoption, enhancing decision-making speed and accuracy. Specifically, firms with robust MAMD systems report a 15% improvement in decision-making efficiency and a 10% increase in return on assets. These findings underscore MAMD's role in boosting performance in VMMEs and highlight the need for targeted strategies to facilitate its adoption. This study adds to the literature by providing a framework for integrating management accounting in industry-specific contexts, promoting sectoral growth and sustainability.